Using American Coming-of-Age Stories in the ELT Classroom - Elena Ortells Montón (CLELEjournal, 2017)
Reading constitutes solid grounds for the development of basic language and critical skills as well as for the improvement of Intercultural Communicative Competence. However, in a world dominated by visual media and technology, getting young people to read becomes a challenging experience, which turns out to be even more problematic in English language teaching. Young adult literature and multicultural coming-of-age stories can offer teachers the necessary materials to foster interest in reading and to raise intercultural awareness. In spite of its limited scope, the project reported in this article proved that a conscientious choice of extracts taken from Yang's American Born Chinese, Alexie's The Absolutely True Diary of a Part-Time Indian, Cisneros's The House on Mango Street and Morrison's The Bluest Eye, among others, could contribute to improving language learners' linguistic and sociocultural competence. The project employed an interactive methodology based on a combination of critical multicultural pedagogy and reader-response theory, centering on the students' perspectives of their learning experience. While this experience did not answer the question whether the learners' reading competence had in fact increased, the students themselves acknowledged a substantial increase in reading motivation and confidence as well as cultural awareness.